Early Childhood Vocabulary Acquisition through Multimodal Strategies: A Semiotic Study of Miss Rachel - Thalita Shafira Azhari; Rohmani Nur Indah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
In this digital era, YouTube Kids has become one of the applications most frequently used by children with a variety of content, some aimed at education and others at entertainment. This research analyzes educational videos specifically for children to examine the multimodal strategies in Miss Rachel's YouTube educational videos that support early childhood vocabulary acquisition. It uses Kress and Leeuwen (2006) multimodality theory, which includes seven semiotic modes: linguistic, visual, gestural, audio, spatial, temporal, and three-dimensional. The method used is descriptive qualitative, with data consisting of video footage of Miss Rachel introducing vocabulary through various multimodal strategies. The results show that each mode contributes meaningfully to the vocabulary learning process. All modes support each other and create a fun, interactive, and meaningful learning experience for children. This research concludes that multimodal strategies in Miss Rachel videos effectively support vocabulary acquisition in early childhood. It also recommends that educators, parents, and digital content developers consider using multimodal approaches in children's language learning activities.